Counselling Skills and Studies - Dykes, Fiona Ballentine; Kopp, Barry; Postings, Traci; Crouch, Anthony (Los Angeles : SAGE, 2014)
Packed full of practical activities and written in a supportive conversational style, this book is essential reading for anyone wanting to learn counselling skills or embarking on their first stage of training to be a counsellor.
Keywords: Counseling; Society